Effect of airflow conditions on growth and simultaneously DHA and squalene production by Aurantiochytrium sp. PRA-276 - Paulo, M.C. (2021)
There has been a growing trend worldwide in the use of squalene and docosahexaenoic acid (DHA), due in part to their recognized health benefits and their range of applications. However, the growth of the industry exploiting these resources has been extremely limited by the scarcity and limitations of raw material, leading to the need to develop more sustainable sources of production. Aurantiochytrium sp. PRA-276, with the ability to produce high concentrations of DHA and squalene, is a promising candidate for the commercial production of these biomolecules. The aim of this study was to determine the cumulative effect of airflow levels and stirring speed of Aurantiochytrium sp. PRA-276 biomass during DHA and squalene production. Different airflow levels (3, 6 and 9 L min-1) and two stirring speeds (150 and 300 rpm) were investigated. The highest biomass production was achieved after 96 hours with 300 rpm stirring speeds and airflow level of 9 L min-1. The maximum total lipids content reached 61.4% of the dried biomass, and the optimal parameters for DHA and squalene production were stirring speed 150 rpm and airflow level 3 L min-1. The maximum yield of DHA production was 4.3 g L-1 at 96 h of fermentation. The highest yield of squalene production was 762.5 mg L-1 at 48 hours of growth. The results show that Aurantiochytrium sp. PRA-276 is a promising resource for microbial DHA and squalene production due to the high yield of DHA and squalene that it generates. Moreover, the capacity for large-scale fermentation of this organism could be useful for the synthesis of biomass related products with high added value.